Generation of the lower-thermospheric vertical wind estimated with the EISCAT KST radar at high latitudes during periods of moderate geomagnetic disturbance - Oyama, S.; Watkins, B. J.; Maeda, S.; Shinagawa, H.; Nozawa, S.; Ogawa, Y.; Brekke, A.; Lathuillere, C.; Kofman, W. (Annales Geophysicae, 2008)
Lower-thermospheric winds at high latitudes during moderately-disturbed geomagnetic conditions were studied using data obtained with the European Incoherent Scatter (EISCAT) Kiruna-Sodankylä-Tromsø (KST) ultrahigh frequency (UHF) radar system on 9–10 September 2004. The antenna-beam configuration was newly designed to minimize the estimated measurement error of the vertical neutral-wind speed in the lower thermosphere. This method was also available to estimate the meridional and zonal components. The vertical neutral-wind speed at 109 km, 114 km, and 120 km heights showed large upward motions in excess of 30 m s−1 in association with an ionospheric heating event. Large downward speeds in excess of −30 m s−1 were also observed before and after the heating event. The meridional neutral-wind speed suddenly changed its direction from equatorward to poleward when the heating event began, and then returned equatorward coinciding with a decrease in the heating event. The magnetometer data from northern Scandinavia suggested that the center of the heated region was located about 80 km equatorward of Tromsø. The pressure gradient caused the lower-thermospheric wind to accelerate obliquely upward over Tromsø in the poleward direction. Acceleration of the neutral wind flowing on a vertically tilted isobar produced vertical wind speeds larger by more than two orders of magnitude than previously predicted, but still an order of magnitude smaller than observed speeds.